MONITORING THE IMPACT OF INTENSIFICATION OF AGRICULTURAL LAND USE ON THE QUALITY OF SOILS OF UKRAINE - Tetiana YASHCHUK; Olena KORCHYNSKA; Borys SYDORUK; Halyna SYDORUK; Mariia HORUN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article examines the influence of intensification of agricultural activities on soil quality, the dependence of humus content in soils on the dynamics of the technically available energy potential of crops grown in Ukraine in the regional context, as well as amount of organic fertilizers that can obtain from farm animal. A decrease in the humus content in the soils of Ukraine was established according to the obtained results. It is primarily due to increasing cultivation of soil-depleting crops and reducing the number of farm animals, waste products of which can use to restore land fertility. This situation leads to a loss of natural fertility of agricultural land and a decrease in their monetary value. It will require significant financial costs to further restore the quality characteristics of Ukraine's soils. The paper used a wide range of methods of statistical analysis, grouped administrative regions into clusters according to the study. Research data reveal a high correlation coefficient of the studied indicators within individual territories. The research results are expected to be used to plan the necessary measures to increase the environmental and economic efficiency of the agricultural land use system.